N2 Fixation and New Insights Into Nitrification From the Ice-Edge to the Equator in the South Pacific Ocean - Raes, Eric J.; van de Kamp, Jodie; Bodrossy, Levente; Fong, Allison A.; Riekenberg, Jessica; Holmes, Bronwyn H.; Erler, Dirk V.; Eyre, Bradley D.; Weil, Sarah-Sophie; Waite, A. M. (Frontiers in Marine Science, 2020)
Nitrogen (N) is an essential element for life and controls the magnitude of primary productivity in the ocean. In order to describe the microorganisms that catalyze N transformations in surface waters in the South Pacific Ocean, we collected high-resolution biotic and abiotic data along a 7000 km transect, from the Antarctic ice edge to the equator. The transect, conducted between late Austral autumn and early winter 2016, covered major oceanographic features such as the polar front (PF), the subtropical front (STF) and the Pacific equatorial divergence (PED). We measured N2 fixation and nitrification rates and quantified the relative abundances of diazotrophs and nitrifiers in a region where few to no rate measurements are available. Even though N2 fixation rates are usually below detection limits in cold environments, we were able to measure this N pathway at 7/10 stations in the cold and nutrient rich waters near the PF. This result highlights that N2 fixation rates continue to be measured outside the well-known subtropical regions. The majority of the mid to high N2 fixation rates (> 20nmol L-1 d-1), however, still occurred in the expected tropical and subtropical regions. High throughput sequence analyses of the dinitrogenase reductase gene (nifH) revealed that the nifH Cluster I dominated the diazotroph diversity throughout the transect. nifH gene richness did not show a latitudinal trend, nor was it significantly correlated with N2 fixation rates. Nitrification rates above the mixed layer in the Southern Ocean ranged between 56 and 1440 nmol L-1 d-1. Our data showed a decoupling between carbon and N assimilation (NO3- and NH4+ assimilation rates) in winter in the South Pacific Ocean. Phytoplankton community structure showed clear changes across the PF, the STF and the PED, defining clear biomes. Overall, these findings provide a better understanding of the ecosystem functionality in the South Pacific Ocean across key oceanographic biomes.